Elaboration of the preliminary Rheumatoid Arthritis Impact of Disease (RAID) score: a EULAR initiative. Issue 11 (3rd December 2008) - Gossec, L; Dougados, M; Rincheval, N; Balanescu, A; Boumpas, D T; Canadelo, S; Carmona, L; Daurès, J-P; de Wit, M; Dijkmans, B A C; Englbrecht, M; Gunendi, Z; et al.
Abstract : Background: Current response criteria in rheumatoid arthritis (RA) usually assess only three patient-reported outcomes (PROs): pain, functional disability and patient global assessment. Other important PROs such as fatigue are not included. Objective: To elaborate a patient-derived composite response index for use in clinical trials in RA, the RA Impact of Disease (RAID) score. Methods: Ten patients identified 17 domains or areas of health relevant for inclusion in the score, then 96 patients (10 per country in 10 European countries) ranked these domains in order of decreasing importance. The seven most important domains were selected. Instruments were chosen for each domain after extensive literature research of psychometric properties and expert opinion. The relative weight of each of the domains was obtained from 505 patients who were asked to "distribute 100 points" among the seven domains. The average ranks of importance of these domains were then computed. Results: The RAID score includes seven domains with the following relative weights: pain (21%), functional disability (16%), fatigue (15%), emotional well-being (12%), sleep (12%), coping (12%) and physical well-being (12%). Weights were similar across countries and across patient and disease characteristics. Proposed instruments include the Health Assessment Questionnaire and numerical ratings scales. Conclusion: The preliminary RAID score is a patient-derived weighted score to assess the impact of RA. An ongoing study will allow the final choice of questionnaires and assessment of validity. This score can be used in clinical trials as a new composite index that captures information relevant to patients.